Color Change and Cytotoxic Effects of a Bleaching Gel With 22% Carbamide Peroxide Catalyzed by Manganese Oxide - de Oliveira Ribeiro, Rafael Antonio [UNESP]; Peruchi, Victória [UNESP]; Sônego, Leonardo Novaes Gaeta [UNESP]; Soares, Igor Paulino Mendes [UNESP]; Soares, Diana Gabriela; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Wiley, 2025)
Objectives: To evaluate the color change and trans-amelodentinal cytotoxicity of a 22% carbamide peroxide (CP) bleaching gel containing different concentration of manganese oxide (MnO2). Material and Methods: Enamel/dentin discs adapted to artificial pulp chambers were distributed according to treatments: CN—No treatment; CP22%–22%CP; CP22 + 2MnO2–22%CP + 2 mg/mLMnO2; CP22% + 6MnO2–22%CP + 6 mg/mLMnO2; CP22% + 10MnO2–22%CP + 10 mg/mLMnO2 applied for 2 h for 15 days. Color change—CC (ΔE00 and ΔWID) (n = 8) was determined at 5, 10, and 15-day periods (ANOVA/Sidak). Trans-amelodentinal cytotoxicity (TC) was assessed after applying the extracts to cultured MDPC-23 cells, which were analyzed concerning their viability (Vi) (n = 8) and oxidative stress (OxS) (n = 8). The amount of hydroxyl radical (OH•) (n = 4) generated by H2O2 degradation (ANOVA/Sidak), and trans-amelodentinal diffusion of H2O2 (n = 8) (ANOVA/Tukey) were also evaluated. Results: CP22 + 10MnO2 presented higher CC than CP22 for both evaluated equations in all analysis periods (p ≤ 0.04). Among bleached groups, CP22 + 10MnO2 presented the highest OH• generation (p ≤ 0.02) and the lowest trans-amelodentinal diffusion of H2O2 (p ≤ 0.0004). Therefore, MDPC-23 cells in CP22 + 10MnO2 exhibited the lowest OxS (p < 0.0001) and consequently the highest Vi (p ≤ 0.0146). Conclusion: Besides increasing the bleaching efficacy, the strategy of adding 10 mg/mL of MnO2 to a 22%CP bleaching gel also reduces significantly the trans-amelodentinal diffusion of H2O2, diminishing the cytotoxicity caused by at-home bleaching therapy. Clinical Significance: The addition of MnO2 to a 22% carbamide peroxide bleaching gel improves the color change and reduces the cytotoxicity effects of the product, making at-home bleaching faster and biologically safer.
Keywords: cell culture; dental materials; tooth bleaching; toxicity